STUDI DESKRIPTIF SIKAP TELITI DALAM PEMBUATAN KARYA MOZAIK PADA PEMBELAJARAN SENI RUPA KELAS IIIB SD NEGERI 19 KOTA BENGKULU - Yesi Susanti; Pebrian Tarmizi; Irfan Supriatna (STKIP Subang, 2026)
This study aims to describe the careful attitude in creating mosaic works in art education for third-grade students at SD Negeri 19 Kota Bengkulu. This is a qualitative study using descriptive methods. The subjects of this study were 30 third-grade students divided into six groups. The research instruments were the researcher himself and observation, interviews, and documentation guidelines. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and data verification. Data validity was obtained by using triangulation techniques and member checks. The results of this study show that students' carefulness in making mosaic artworks can be observed through four indicators, namely: (1) concentration when working or doing something, (2) being careful and not rushing, (3) working or doing activities systematically, (4) working on and completing a task. From the results of observations and interviews, it was found that there were four groups that were able to consistently demonstrate all four indicators during the mosaic-making process. Meanwhile, the other two groups experienced obstacles and difficulties in preparing tools and materials, applying glue, and attaching seeds. Thus, it can be concluded that most students demonstrated a meticulous attitude in making mosaics.